2018
DOI: 10.1016/j.msard.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

High intensity interval training for people with multiple sclerosis: A systematic review

Abstract: HIIT appears to be safe and effective in increasing fitness in people with MS and low levels of disability. Further research is required to explore the effectiveness of HIIT in people with progressive MS and in those with higher levels of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 48 publications
1
44
0
1
Order By: Relevance
“…The greatest strength of the present study is that it provides an up-to-date and extensive quantitative overview of the literature regarding the efficacy of different exercise interventions in patients with chronic brain disorders. Second, our findings are largely in accordance with previous (quantitative) reviews that synthesized evidence on the efficacy of physical exercise in the studied brain disorders [20,22,24,25,28,252]. However, in contrast to previous work, we performed both transdiagnostic and within-disorder analyses and evaluated the effect of several moderators providing evidence that physical exercise can be considered as an effective add-on and transdiagnostic treatment.…”
Section: Strengths and Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…The greatest strength of the present study is that it provides an up-to-date and extensive quantitative overview of the literature regarding the efficacy of different exercise interventions in patients with chronic brain disorders. Second, our findings are largely in accordance with previous (quantitative) reviews that synthesized evidence on the efficacy of physical exercise in the studied brain disorders [20,22,24,25,28,252]. However, in contrast to previous work, we performed both transdiagnostic and within-disorder analyses and evaluated the effect of several moderators providing evidence that physical exercise can be considered as an effective add-on and transdiagnostic treatment.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…In contrast, research on the efficacy of physical exercise in treatment of other brain disorders is still in its infancy and therefore not part of the standard care. Although several studies have investigated the effect of physical exercise in different chronic brain disorders such as Alzheimer's disease (AD) [17,18], multiple sclerosis (MS) [19][20][21], Parkinson's disease (PD) [22,23], Schizophrenia (Sz) [24,25] and unipolar depression (UD) [26][27][28], results and mainly recommendations for clinical practice have been highly diverse [29]. As a consequence, current evidence for efficacy of exercise therapy is still disputed and exercise is not part of the regular care offer for patients with aforementioned disorders in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…The expert panel noted a recent trend for recommendation of HIIT among people with MS and post-stroke. Indeed, two resources suggested one weekly session of high intensity training up to 90% of VO 2peak can be prescribed for people with MS. 19,21 This was supported by a recent systematic review that demonstrated HIIT was a safe and effective means for increasing fitness in people with higher functioning MS. 54 Regarding people with stable, chronic stroke, one resource acknowledged that HIIT can elicit greater training effects and should be performed when safe and well tolerated. 28 Benefits from HIIT for people post-stroke may include improved functional, cardiovascular, and neuroplastic outcomes.…”
Section: Notable Trendsmentioning
confidence: 99%
“…In MS, avoiding overheating seems highly relevant as it may induce the so called Uhthoff phenomenon leading to nerve conduction disturbances. Even interval high intensity training has been shown to be safe and effective in patients with MS with already relevant disability (Campbell, Coulter & Paul, 2018). However, while numerous studies now have shown beneficial effects of exercise training on physical capacity, strength, quality of life, mood (Latimer-Cheung et al, 2013) and fatigue in MS (Heine et al, 2015), high quality clinical trials focusing on cognitive function are scarce and the evidence is not conclusive (Sandroff et al, 2016).…”
Section: Introductionmentioning
confidence: 99%